Product diversity and spectrum of choice in hospital ePrescribing Systems in England. - Hajar Mozaffar; Robin Williams; Kathrin Cresswell; Zoe Morison; Ann Slee; Aziz Sheikh; ePrescribing Programme (PLoS ONE)
Background ePrescribing systems have considerable potential for improving healthcare quality and safety. With growing expectations about the benefits of such systems, there is evidence of widespread plans to implement these systems in hospitals in England where hitherto they have had a low uptake. Given the international drive away from developing home-grown to systems to procuring commercial applications, we aimed to identify available ePrescribing systems in England and to use the findings to develop a taxonomy of the systems offered by suppliers. Methods and findings We undertook a scoping review of the published and grey literature, and conducted expert interviews with vendors, healthcare organisations and national ePrescribing experts in order to identify the spectrum of available systems, identify and map their key features, and then iteratively develop and validate a taxonomy of commercial ePrescribing systems available to English hospitals. There is a wide range of available systems including 13 hospital-wide applications and a range of specialty systems. These commercial applications can be grouped into four sub-categories: standalone systems, modules within integrated systems, functionalities spread over several modules, and specialty systems. The findings also reveal that apart from four packaged applications (two of which are specialty systems), all other systems have none or less than two live implementations across England. Conclusions The wide range of products developed in the last few years by different national and international suppliers, and the low uptake of these products by English hospitals indicate that the English ePrescribing market is still in its infancy. This market is undergoing rapid cycles of change, both with respect to the number of suppliers and their diversity of offerings. Constant renewal of knowledge is needed on the status of this evolving market, encompassing the products development and adoption, to assist implementation decisions and facilitate market maturity.